Trading Places: Mobility Responses of Native and Foreign-Born Adults to the China Trade Shock - David Autor; David Dorn; Gordon H. Hanson (Institute of Labor Economics (IZA), 2024)
Previous research finds that the greater geographic mobility of foreign than native-born workers facilitates labor market adjustment to shifting regional economic conditions. We examine immigration's role in enabling U.S. commuting zones to respond to manufacturing job loss caused by import competition from China. Although foreign-born population headcounts fell by a larger proportion than those of the native-born in trade-exposed regions, the contribution of immigration to labor market adjustment in this episode was small. Because most U.S. immigrants arrived in the country after manufacturing regions were already mature, few took jobs in industries that later saw import surges. The foreign-born population share in regions with high trade exposure was only three-fifths that in regions with low exposure. Immigration may do more to aid adjustment to cyclical shocks, in which job loss follows recent hiring booms, than to aid adjustment to secular decline, in which hiring booms occurred longer ago.
Keywords: E24; F14; F16; J23; J31; L60; O47; R12; R23; 330; immigration; import competition; geographic labor mobility; manufacturing decline; job loss